1988
DOI: 10.1007/bf00612722
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aggressive encounters on pineal melatonin formation in male gerbils (Meriones unguiculatus, Cricetidae)

Abstract: Pineal N-acetyl-transferase activity and radioimmunoassayable melatonin levels were determined in adult male gerbils subjected to aggressive encounters using the intruder-model. In the first experiment, a single encounter of 3 min was applied in the afternoon to intact and to animals with sympathetically denervated pineal organs. Compared with controls, both stressed groups demonstrated a drastic decrease in N-acetyl-transferase activity followed by a slow recovery. In both groups there also occurred a marked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…An interesting experiment by Heinzeller et al 37 examined the effects of single and repeated aggressive encounters on the synthesis of MLT in the pineal gland. The authors found an elevation of MLT immediately at the end of the encounter, followed by a decline in the levels of the neurohormone.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting experiment by Heinzeller et al 37 examined the effects of single and repeated aggressive encounters on the synthesis of MLT in the pineal gland. The authors found an elevation of MLT immediately at the end of the encounter, followed by a decline in the levels of the neurohormone.…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin, a hormone produced by the pineal gland, is a substance that seems to have a special relationship to tonic immobility. Thus, as mentioned above, exposure to stress (e.g., aggression, temperature changes) increases melatonin production in a number of species (Heinzeller et al, 1988; Lynch & Deng, 1986). Moreover, the duration of tonic immobility correlates positively with the cycle of melatonin release in many species; these species are more susceptible to tonic immobility during the night (Hennig & Dunlap, 1977a, 1977b).…”
Section: Control Mechanisms Of Tonic Immobility and Muscular Atoniamentioning
confidence: 95%
“…Melatonin is also implicated in the tonic immobility reaction. It has been found that exposure to aggression and stress increases melatonin production in a number of species (Heinzeller, Joshi, Nürnberber, & Reiter, 1988; Lynch & Deng, 1986). Similarly, melatonin injections directly potentiate the tonic immobility reaction (Hennig et al, 1979; Hennig, Harston, & Dunlap, 1980).…”
Section: Auxiliary Factsmentioning
confidence: 99%
“…The unique social behavior and the ecological niche the species occupies may be other reasons for the varied results. In Mongolian gerbils the aggressive encounters are known to affect pineal biosyn thesis of melatonin [27]. The Indian desert gerbil too exhibits aggressive and conflict be havior [28].…”
Section: Discussionmentioning
confidence: 99%